Success of long-term restoration of degraded arid land using native trees planted 11 years earlier (2020)
Background and aims Restoration of degraded desert soil with three species of legume trees and the giant cardon cactus was evaluated 11 years after planting in the southern Sonora Desert. Methods The trees in six independent field experiments were grown individually or in combination of a legume tree and cardon cactus and were originally treated with plant growth-promoting bacteria, arbuscular mycorrhizal fungi, or small amounts of cattle compost or a combination of all treatments. Survival and height of trees and cacti and cactus biovolume were measured. Results When data were combined from all experiments and analyzed together, the best survivor was the cardon cacti and, to a lesser extent, the legume tree mesquite amargo. Over a decade later, a combination of a legume tree with cardon cactus, while detrimental to the legume, significantly increased the chances of the cactus to survive and grow in degraded soil. The biotic and compost treatments, while enhancing the initial establishment of the plants in 2004, had only marginal benefit on the growth of cactus 11 years later. Conclusions Long-term desert restoration with native trees is possible. Because this cactus is the native, long term soil stabilizer, a combination cactus-legume tree is recommended for long term desert restorations.